The interdecadal variation of the relationship between ENSO and the IOD’s eastern and western poles around 2000 - Xuelun Huang; Xuelun Huang; Li Yan; Li Yan; Jianjun Xu; Jianjun Xu; Shaojun Zheng (Frontiers in Marine Science)
The El Niño-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) coupling exhibits important globe climate impacts. The relationship of ENSO with the IOD’s eastern pole (EP) and western pole (WP) and its interdecadal variation have not been determined. Based on observations and reanalysis datasets, this study reveals that the ENSO and IOD-EP relationship significantly weakened, while the ENSO and IOD-WP relationship strengthened after 2000. Changes in ENSO-IOD-EP connection outweigh that in ENSO-IOD-WP connection. The El Niño-positive IOD (pIOD) coupling weakened and the La Niña-negative IOD (nIOD) coupling strengthened. In addition, the changes in El Niño-pIOD coupling dominate. From the atmospheric view, an anomalous ascending branch of Walker circulation in the Maritime Continent intensified after 2000. The new status of Walker circulation favored weakened wind easterlies and SST warming in IOD-EP, which hindered the development of pIOD events but promoted the development of nIOD events. From the oceanic wave process view, the equatorial and extra-equatorial downwelling Rossby waves both favored SST warming in IOD-WP after 2000, which promoted the generation of pIOD events but hindered the generation of nIOD events. The equatorial Rossby waves reflected by Kelvin waves may be even more dominant in regulating the evolution of IOD events. The presence of the Seychelles thermocline dome region amplifies the impact of oceanic wave processes. Using information flow, a causal analysis verifies that the influence of atmospheric processes on IOD-EP decreased and the influence of oceanic wave processes on IOD-WP increased. Such weakened ENSO-IOD-EP connection can be attributed to the weakened wind easterlies in pIOD events associated with the La Niña-like condition in Pacific and the declined Bjerknes feedback induced by the deepened thermocline condition in IOD-EP. While the strengthened ENSO-IOD-WP connection can be attributed to the strengthened downwelling Rossby waves in pIOD events, which were related to IO Basin (IOB) warming induced by El Niño in the previous year. Increased consecutive El Niños associated with La Niña-like condition are favorable for an enhanced ENSO-pIOD-WP connection. Under the background of ENSO properties transition occurring around 2000, our research will contribute to a better understanding on the ENSO-IOD coupling and its implications.